Analisis Swamedikasi Tingkat Pengetahuan, Sikap, Dan Praktik Masyarakat Terhadap Obat Diare Di Klinik Mustopa Cilame - Indi Yutina; Dewi Wulantresna (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Diarrhea is a health issue frequently managed through self-medication. The success of self-medication depends on the public's knowledge, attitudes, and practices regarding the rational use of antidiarrheal drugs. This study aimed to analyze the public's knowledge, attitudes, and practices concerning antidiarrheal self-medication, as well as the relationships and influences between these variables at the Mustopa Cilame Clinic. A quantitative method with a descriptive-analytic design was employed. Sixty respondents were selected using simple random sampling. Data were collected via a questionnaire that had passed validity and reliability testing (Cronbach's Alpha = 0.810). The results indicated that the majority of respondents fell into the